Asthma predictive index as a useful diagnostic tool in preschool children: a cross-sectional study in Korea - Dong Hyeon Lee; Ji-Won Kwon; Hyung Young Kim; Ju-Hee Seo; Hyo-Bin Kim; So-Yeon Lee; Gwang-Cheon Jang; Dae-Jin Song; Woo Kyung Kim; Young-Ho Jung; Soo-Jong Hong; Jung Yeon Shim (The Korean Pediatric Society, 2020)
Background It is challenging to diagnose asthma in preschool children. The asthma predictive index (API) has been used to predict asthma and decide whether to initiate treatment in preschool children. Purpose This study aimed to investigate the association between questionnaire-based current asthma with API, pulmonary function, airway hyperreactivity (AHR), fractional expiratory nitric oxide (FeNO), and atopic sensitization in preschool children. Methods We performed a population-based cross-sectional study in 916 preschool children aged 4-6 years. We defined current asthma as the presence of both physician-diagnosed asthma and at least one wheezing episode within the previous 12 months using a modified International Study of Asthma and Allergies in Childhood questionnaire. Clinical and laboratory parameters were compared between groups according to the presence of current asthma. Results The prevalence of current asthma was 3.9% in the study population. Children with current asthma showed a higher rate of positive bronchodilator response and loose and stringent API scores than children without current asthma. The stringent API was associated with current asthma with 72.2% sensitivity and 82.0% specificity. The diagnostic accuracy of the stringent API for current asthma was 0.771. However, no intergroup differences in spirometry results, methacholine provocation test results, FeNO level, or atopic sensitization rate were observed. Conclusion The questionnaire-based diagnosis of current asthma is associated with API, but not with spirometry, AHR, FeNO, or atopic sensitization in preschool children.